The local environment of Co 2+ ions intercalated in vanadium oxide/hexadecylamine nanotubes - Saleta, Martin Eduardo (2012)
Vanadium oxide nanotubes constitute promising materials for applications in nanoelectronics as cathode materials, in sensor technology and in catalysis. In this work we present a study on hybrid vanadium oxide/hexadecylamine multiwall nanotubes doped with Co ions using state of the art x-ray diffraction and absorption techniques, to address the issue of the dopant location within the nanotubes structure. The x-ray absorption near-edge structure analysis shows that the Co ions in the nanotubes are in the 2+ oxidation state, while extended x-ray absorption fine structure spectroscopy reveals the local environment of the Co2+ ions. Results indicate that Co atoms are exchanged at the interface between the vanadium oxide layers and the hexadecylamines, reducing the amount of amine chains and therefore the interlayer distance, but preserving the tubular shape. The findings in this work are important for describing Co2+ interaction with vanadium oxide nanotubes at the molecular level and will help to improve the understanding of their physicochemical behavior, which is desired in view of their promising applications.